TACTICS AND TREATMENT FOR ACUTE ANAEROBIC PARAPROCTITIS - Sherkulov K.U.; Bobokulov A.U; Usmonkulov M.K.; Babakulova F.U. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Acute paraproctitis is the most complex form of purulent inflammatory processes. When local clinical manifestations of the disease are mild, such patients are often misdiagnosed, which often leads to untimely and sometimes incorrect surgical treatment. Acute horseshoe-shaped paraproctitis, despite treatment, often ends in the formation of a complex horseshoe-shaped fistula and purulent cavities and leaks.